IMPROVING MEDICATION ADHERENCE AS INDICATED BY BTA TEST IN TUBERCULOSIS PATIENTS USE MOTIVATIONAL INTERVIEWING - Santoso, Shelfi Dwi Retnani Putri; Agustine, Uly; Mugianti, Sri; Paju, Wanto (Universitas Aisyah Pringsewu, 2023)
Low adherence to TB medication can also lead to the development of drug resistance, making treatment more challenging. There is a need for a specific approach to TB patients to enhance motivation in anti-tuberculosis treatment, including the innovation of providing motivational interviewing (MI). This study aims to determine the impact of MI on the treatment adherence of tuberculosis patients as indicated by the BTA test. The research method used a quasi-experimental design with a control group. The population consisted of 60 respondents using consecutive sampling techniques, divided into 30 experimental groups and 30 control groups. Descriptive analysis was used to depict the deviation in the percentage of gender, age, and education, while the difference test employed the Wilcoxon Signed Ranks Test. The results indicated that both the experimental and control groups consisted mostly of males, with 16 (53.3%) and 17 (56.7%), respectively, and individuals over 41 years of age, with 23 (76.7%) and 21 (70%), respectively. Meanwhile, the difference test showed that the treatment group had a p-value of 0.000, indicating a significant difference in treatment adherence before and after the intervention. Discussion: MI communication can increase clients' motivation to engage in positive behavior’s, such as adhering to treatment, which can lead to negative BTA test results. Conclusion: This intervention can be recommended as an additional approach to improving treatment adherence in tuberculosis patients.